Complexity And Socialization Of Taxation Rule In Affecting The Taxpayer Accounting Behaviour In Indonesia - Tarjo, Tarjo (The International Journal of Accounting and Business Society, 2009)
Complexity in this study refers to the numbers and varieties of elements related to taxation rule. Socialization refers to mentoring which organized by tax-institution (Fiscus) through the counseling for taxation practice, service and control. Taxpayer obedience is one of taxation success measurement. Complexity and socialization taxation rule influences taxpayer obedience in fulfilling their taxation obligation. The complexity of taxation rule will be tricky for the taxpayer for understanding taxation. The lack of socialization on taxation rule will make the taxpayer flustered to counting, make payment, and deposit their tax burden. In favor of these difficulty and confemployedness, the taxpayer needs assistance from professional on taxation. Their assist will improve obedience cost and encourage the taxpayer to generate accounting artificial to minimize taxes. The greater obedience cost and enlarger accounting artificial will encourage the taxpayer for being more disobey. Keywords: Taxpayer, Complexity, Socialization, Taxation rules, Accounting behavior, Obedience cost, Obedience.